الأحكام القانونية لقسمة المهايأة بين الفقه الإسلامي والقوانين الوضعية - الفتلاوي، صاحب عبيد (الجمعية العلمية للبحوث والدراسات الاستراتيجية, 2011)
علي الرغم من كراهة المشرع لوجود المال الشائع بسبب اختلاف الشركاء في إدارة واستغلال هذا المال، وهو ما يتسبب في عرقلة استثماره بالشكل الأمثل بما يخدم الاقتصاد الوطني، فإن وجود ظاهرة الشيوع. ولكي يقلل المشرع من مساوئ هذا النوع من الملكية وضع الكثير من المعوقات أمام ازديادها وفي طليعتها اشتراطه عدم جواز الاتفاق على الشيوع إلا لمدة معينة لا يجوز تجاوزها، بالإضافة إلى إجازته قسمة المهايأة للحيلولة دون بقاء المال معطلاً. \ وفي هذا البحث سوف نؤكد على مفصل واحد من هذا الموضوع وهو الأحكام القانونية لقسمة المهايأة من خلال مناقشة الأحكام المتعلقة بالمتقاسمين وإثبات هذا النوع من القسمة والاحتجاج بها عفى الغير وأخيراً حالات انقضاء هذا الوع من القسمة. كل ذلك سيكون بدراسة مقارنة بين الفقه الإسلامي والقوانين الوضعية، وهو موضوع عز على المكتبة العربية وجوده وشحت البحوث فيه مما دفع الباحث إلى اختياره. Although the legislator believes that there are many advantages about the prevalent ownership of a property, because of its partners disagreement about the management & use of this property' the block its investment to serve the national economy, but this phenomenon became a fact. And because there are many conditions where we can find many people having the prevalent property, the legislator tried many times to minimize this kind of property to prevent its negative results by limiting the period of having this property the way it is and permitting the partners to use their rights in what we call (Division of benefits) w'hich put the property' in a dynamic state. \ Jn this research we will take one part of this subject in details, discussing the legal provisions of apportionment of benefit: including legal provisions related to partners, also proving this kind of division and using it to protest against others. Finally we will discuss the expiration slates of this type of division. \ All this would be provided by a comparative study between Islamic jurisprudence and civil laws. \ The main reason for choosing this subject that it is truly lacked in the Arab library and almost there are no researches about it.
Keywords: الفقه الإسلامي -- الأحكام الشرعية -- القوانين والتشريعات -- الأحكام القضائية -- قسمة المهايأة